Possibili in the light of Article 40 of the Convention on the Rights of the Child (Academic Journal of Internal Affairs, 2021)
Article 40 of the Convention on the Rights of the Child lays down guarantees applicable to criminal proceedings against juveniles. The Article on juvenile justice focuses on children suspected, accused or convicted of a crime. Among the guarantees of the rights of the child in the proceedings, the Convention emphasizes the possibility for occasional diversions from the judicial processes. For example, the institution of preventive patronage, which entered the Hungarian legal system in 2015, is indeed such a new route of diversion. Preventive patronage has been legal in Hungary since the 1st of January 2015. This new legal institution has roots in Hungarian criminal law, and its placement into the system of child protection was based on the authorization of the 1430/2011. (XII. 13.) governmental decision, despite the fact that the reasons for establishing it in the first place were to reduce child and juvenile crime and to reintegrate perpetrators. The following study highlights the relationship between preventive patronage and the criminal proceedings against juvenile perpetrators.The author examines the rights of children in situations of ordering and enforcing preventive patronage and draws attention to the dangers of premature intervention and subsequent stigmatization.
Keywords: child protection; authority measure; crime prevention; probation service